2016
DOI: 10.1007/978-3-319-41754-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Structure of Tables in Scientific Literature

Abstract: Abstract. Within the scientific literature, tables are commonly used to present factual and statistical information in a compact way, which is easy to digest by readers. The ability to "understand" the structure of tables is key for information extraction in many domains. However, the complexity and variety of presentation layouts and value formats makes it difficult to automatically extract roles and relationships of table cells. In this paper, we present a model that structures tables in a machine readable w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 24 publications
(22 reference statements)
0
58
0
Order By: Relevance
“…Most authors differentiate between data tables, which provide data to be extracted, and non-data tables, which are used for layout purposes or to provide utilities. Many of them make also a difference between listings, forms, matrices, and enumerations [16,18,26,30,34,44,46,66], although the exact terminology used is very diverging; there is also a proposal in which tables are classified according to whether they have headers or not [22].…”
Section: Table-related Vocabularymentioning
confidence: 99%
See 3 more Smart Citations
“…Most authors differentiate between data tables, which provide data to be extracted, and non-data tables, which are used for layout purposes or to provide utilities. Many of them make also a difference between listings, forms, matrices, and enumerations [16,18,26,30,34,44,46,66], although the exact terminology used is very diverging; there is also a proposal in which tables are classified according to whether they have headers or not [22].…”
Section: Table-related Vocabularymentioning
confidence: 99%
“…Lerman et al [ [22], and Milošević et al [44] did not pay attention to the discrimination task. The other proposals provide sophisticated approaches.…”
Section: Discriminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure retrieval has been considered, mainly focusing on using text from figure captions (Hearst et al, 2007), text within figures (Rodriguez-Esteban and Iossifov, 2009), as well as text from paragraphs discussing the figures and NER (Demner-Fushman et al, 2012). Research on information extraction from tables is rare (Wong et al, 2009;Peng et al, 2015;Milosevic et al, 2016), though this may change with recent availability of corpora (Shmanina et al, 2016). Jimeno-Yepes and Verspoor (2014) showed that most literature-curated mutation and genetic variant existed only as supplementary material and used open-source PDF conversion tools to extract text from supplementary files for text mining.…”
Section: Challenges and Directionsmentioning
confidence: 99%